Estimation of stresses and cycles to failure of the Tibia during rested and fatigued running - Sasimontonkul, S.; Bay, B. K.; Pavol, M. J. (ISB Congress, 2006)
Many runners suffer from tibial stress fractures. This may be a result of the repetitive loading applied to the tibia during running, as there is evidence of micro-damage in bone tissue after repetitive loading. Therefore, this study investigated 1) whether running-related loads are large enough to cause tibial stress fractures upon repeated application, and 2) whether muscle fatigue alters the potential for tibial stress fractures during running. The potential for tibial stress fractures was predicted, using an integrated experimental and mathematical modeling approach, by estimating the minimum number of loading cycles that would result in the failure of bone (Nfail).